Association between board structure and the value added efficiency of physical and intellectual resources of firms in Malaysia / Nurmala Mustaffa Kamal - Mustaffa Kamal, Nurmala (2005)
This dissertation examines the association between board structure and corporate performance, where performance is defined as the value added (VA) efficiency of the firms' physical and intellectual resources rather than the more commonly used financial terms or profitability ratios. It is argued that the inclusion of intellectual elements into the measurement provides a long-term measurement of corporate performance. The VA efficiency of the firms' total resources is calculated using the Value Added Intellectual Coefficient (VAIC) methodology developed by Ante Pulic (1998). The four board characteristics that are of interest in this study are board composition, directors' ownership, CEO duality and board size. Based on a randomly selected sample of 75 companies listed on the main board of Bursa Malaysia, it is found that board composition and board size have a positive impact on the VA efficiency of firms' total resources, while the effects of directors' ownership and CEO duality on the VA efficiency of firms' total resources are not established. The outcome of the study shows that the emphasis on the importance of independent non-executive directors on the board by the Malaysian Code on Corporate Governance and by the requirements of Bursa Malaysia is deemed very important to the long-term performance of the companies. The study also shows that larger boards function more effectively in Malaysia.